Deadly injustice : Trayvon Martin, race, and the criminal justice system - Johnson, Devon; Warren, Patricia Y.; Farrell, Amy (Amy M.) (New perspectives in crime, deviance, and law., 2015)
The murder of unarmed teenager Trayvon Martin and the subsequent trial and acquittal of his assailant, George Zimmerman, sparked a passionate national debate about race and criminal justice in America that involved everyone from bloggers to mayoral candidates to President Obama himself. With increased attention to these causes, from St. Louis to Los Angeles, intense outrage at New York City's Stop and Frisk program and escalating anger over the effect of mass incarceration on the nation's African American community, the Trayvon Martin case brought the racialized nature of the American justice system to the forefront of our national consciousness. Deadly Injustice uses the Martin/Zimmerman case as a springboard to examine race, crime, and justice in our current criminal justice system. Contributors explore how race and racism informs how Americans think about criminality, how crimes are investigated and prosecuted, and how the media interprets and reports on crime. At the center of their analysis sit examples of the Zimmerman trial and Florida's controversial Stand Your Ground law, providing current and resonant examples for readers as they work through the bigger-picture problems plaguing the American justice system. This important volume demonstrates how highly publicized criminal cases go on to shape public views about offenders, the criminal process, and justice more generally, perpetuating the same unjust cycle for future generations. A timely, well-argued collection, Deadly Injustice is an illuminating, headline-driven text perfect for students and scholars of criminology and an important contribution to the discussion of race and crime in America.